Denying Flight Strategic Options for Employing No-Fly Zones - Mueller, Karl P. (RAND Corporation, 2013)
In the past two decades, the U.S. Air Force has participated in three contingencies involving no-fly zones (NFZs) over Bosnia, Iraq, and Libya, and NFZ proposals have been proffered for some time as an option for intervention in the Syrian civil war that would avoid placing Western troops on the ground. This paper is intended as a preliminary look at NFZs as a strategic approach in such situations, with an emphasis on the forms they might take, their potential utility, and their probable limitations.